Macular Oedema in Idiopathic Macular Telangiectasia Type 1 Responsive to Aflibercept but Not Bevacizumab. (30th September 2014) - Shibeeb, O'Sam; Vaze, Anagha; Gillies, Mark; Gray, Timothy
Abstract : We report a patient with macular oedema due to type 1 macular telangiectasia responding to intravitreal aflibercept injection. A 51-year-old man was diagnosed with type 1 idiopathic macular telangiectasia (IMT) in the right eye. The macular oedema was refractory to initial treatment with intravitreal bevacizumab and argon laser photocoagulation. The patient was then treated with intravitreal aflibercept injections, following which the macular oedema was completely resolved and his vision was significantly improved. Intravitreal aflibercept injection appears to improve vision and reduce persistent macular oedema secondary to type 1 IMT and demonstrated promising anatomical and visual outcomes.